Farmer Field School Approach as a Driver to the Uptake of Climate Smart Agriculture Technologies - Mandaza, McLarence; Magagula, Futhi; Mitti, Joyce (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Smallholder farming in the southern African region is characterised by low agricultural production and productivity, whereas food and nutrition insecurity is characterised by an insecure livelihood activity for most people who depend on it. The challenge confronting the sector is to increase food production and its incomeearning capacity under an increasingly complex climatic environment. Climate change has compounded existing challenges constraining ambition to improve agricultural productivity and the welfare of smallholder farmers even further. The Inter-Governmental Panel on Climate Change (IPCC) forecasts that climate variability and change will severely compromise agricultural production and food access in Africa and other regions. As climate change impacts expand in reach and severity, global food systems face risks of reduced agricultural production, market volatility, and increased threats to rural livelihoods and food security (Foley et al., 2011). To confront these emerging challenges while enhancing agriculture resilience, there is a growing thrust to transform agriculture activities through the wide-scale adoption of climate-smart agriculture (CSA) technologies. The existing wide range of CSA technologies that have the potential to achieve increased production and productivity while enhancing farmers’ resilience and adaptation to climate change provide frontline solutions to improve the state of agriculture production and productivity. A basket of CSA practices that are being promoted reflects emerging best practices across the region. These include conservation agriculture systems encompassing crop rotation and intercropping practices, drought-tolerant crop varieties, seed genetic resource banking, improved fodder production, rainwater harvesting technologies, watershed management, and integrated soil fertility management. Upscaling these CSA practices at the farmer level goes beyond adaptation and mitigation to climate change effects and demands innovative extension approaches to drive the adoption of these practices.